Experimental Demonstration of Software-Configurable Asynchronous Real-Time OFDM Signal Transmission in a Hybrid Fiber-VLLC System - Rui Deng; Jing He; Zhihua Zhou; Jin Shi; Maoxin Hou; Lin Chen (IEEE Photonics Journal, 2017)
In this paper, a real-time hybrid fiber and visible laser light communication orthogonal frequency division multiplexing (OFDM) transport system is experimentally demonstrated. Based on virtual input/output technique, the system can be configured dynamically by using software. Although there is an approximate 12-ppm sampling frequency offset (SFO) between the transmitter and receiver, by adjusting the symbols number of one OFDM frame and the mapping scheme, the experiment results show that without SFO compensation, the system can achieve an up to 2.65 Gb/s data rate with a bit error rate at below 1e-3 after 100-km fiber and 6-m free-space transmission. As far as we know, this is the first time a real-time OFDM transmission has been reported in such a hybrid system.